Our Daily Bread: The Origin of Modern Bread Wheat - Fellowes, Ross (Journal of Scientific Exploration, 2025)
Modern bread wheat, Triticum aestivum, is a hybrid hexaploid that emerged in the Middle East region about 9000 years ago, usually considered to be the result of natural hybridization and multiple allopolyploid speciation. Contrariwise, the abrupt, late appearance of a singular cultivar with traits favoring human utilization suggests the possibility of a directed process, and this paper identifies an ancient Coptic [Egyptian] record specifically detailing the origin of the cultivated [polyploid] wheat plant by human intervention possibly facilitated by radiation.